Microwave detection and imaging of cancer - Ong, Ting Fung. (2009)
Cancer leads the main cause of death for the past 50 years and shows about 7 million cancer deaths worldwide every year. Research simply reflects that there is still rising trend in number of cancer deaths with various treatment methods introduced. With no doubt, breast cancer is one of the most popular women killers regardless of any range of age. Above all, cancer screening plays the most effective roles on controlling the survival rates for these cancer deaths as cancers can be detected and treated early. However, lack of expertise and new reliable invasive screening methods has lead to concern on development of novel cancer diagnostic methods. As a result, a novel parallel-plate waveguide probe is thus proposed to be used as an accurate device for non-invasive dielectric spectroscopy and cancer diagnostics. The parallel-plate waveguide probe is similar to a cut-off section of a transmission line terminated by ground planes. It consists of two metallic plates with flanges spaced apart by dielectric between the plates. Dielectric measurements are performed by placing the aperture onto the material under test (MUT); the admittance or reflected signal S11 is measured by a network analyzer, whereby the complex permittivity of the material under test can be derived from the measurements. In cancer diagnostics, this device is based on detecting the dielectric contrast between a malignant tumor and its surrounding tissues, as the tumor will exhibit different electrical properties (dielectric constant) as compared to normal healthy tissues. Also, altering amplitude of the resonant backscattered signal helps to derive the size and location of the tumor. In this report, parallel-plate waveguide probe is compared with the most widely used technique in non-invasive dielectric spectroscopy using the open-ended coaxial line to illustrate the ability of the probe to measure the complex permittivity of an N-layered media, particularly in biological tissue. Numerical results are presented to compare the proposed methodology in cancer diagnostics.